Use of Transthoracic Ultrasound to Predict Pleural Adhesions: A Prospective Blinded Study - Wei, Bo; Wang, Tao; Jiang, Fusheng; Wang, Huiyu (The Thoracic and Cardiovascular Surgeon, 2012)
Background Detecting pleural adhesions during the preoperative evaluation could greatly aid the surgeon in locating a safe entry site for trocar placement during thoracoscopy. However, there is currently no valid method for this.Objective The aim of the current study was to assess the accuracy of transthoracic ultrasound (TTU) in predicting intrathoracic adhesions prior to thoracic surgery.Material and Method We carried out a diagnostic test study of 117 patients undergoing VATS/thoracotomy. Attempts were made to identify pleural adhesions using TTU by one radiologist. The sites were categorized as “no adhesions” or “adhesions” that with respiration. During operation, adhesions in the area were graded by one surgeon blinded to the original prediction.Results Pleural slide test using TTU had a sensitivity of 88.0 %, a specificity of 82.6 %, and an overall accuracy of 83.8 %. Kappa analysis yielded a significant degree of agreement between the radiologist's predictions and the intraoperative findings with regard to the identification of trocar sites free of pleural adhesions compared to sites with pleural adhesions (p < 0.05).Conclusion TTU can accurately identify intrathoracic adhesions prior to thoracic operation.
Keywords: thoracoscopy/VATS; ultrasound (all applications); pleural disease (incl. drainage); transthoracic ultrasound